Helicopter rotorstrike alerting system - Waanders, T.; Scheiblhofer, R.; Qian, Q.; Noort, B. van; Ziegler, V.; Schubert, F.; Koerber, R. (My University, 2015)
This paper reports on the development of a miniaturized and low-cost, near-field obstacle warning system for helicopters based on mass-market automotive radar technology. This so-called Rotorstrike Alerting System (RSAS) supports the flight crew in detecting obstacles in the direct vicinity of the helicopter (H/C) to avoid main and tail rotor strike accidents. The system is designed as a flight aid to enhance situational awareness and flight safety when manoeuvring in ground or obstacle vicinity possibly under reduced visibility conditions. The activities described herein were performed in the frame of a research project partially funded by the German Federal Ministry for Economic Affairs and Energy (BMWi). Between December 2012 and June 2014 the system concept was elaborated and a prototype system was developed and successfully tested both in ground and flight tests. This paper describes the system concept, its design considerations and it presents first test results.
Keywords: Aircraft Systems, Avionics & Sensors